Analisis terhadap Alternatif Penyelesaian Sengketa (APS) Ditinjau dari Sosiologi Hukum - Harijanto Harijanto (Fakultas Hukum Universitas Islam Jember, 2014)
Conflict, dispute, breach or dispute between or related two individuals or more, has been and will continue to be a common phenomenon in society. The situation will be more troublesome world of law and justice when all the conflict, dispute or disputes to be prosecuted by the justice. Most important in the case of a dispute or disagreement is how to be able to resolve the dispute wise, peaceful and civilized. Dispute resolution outside of court actually has noble values and has practiced in the community in Indonesia. The mechanism actually have a legal basis and has had a precedent and never practiced in Indonesia. The mechanism also has the potential for further development in Indonesia.